2012
DOI: 10.1007/s11033-012-2368-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neurexin and neuroligin in the enteric nervous system and their down-regulated expression levels in Hirschsprung disease

Abstract: To investigate the expression levels of neurexins and neuroligins in the enteric nervous system (ENS) in Hirschsprung Disease (HSCR). Longitudinal muscles with adherent mesenteric plexus were obtained by dissection of the fresh gut wall of mice, guinea pigs, and humans. Double labeling of neurexin I and Hu (a neuron marker), neuroligin 1 and Hu, neurexin I and synaptophysin (a presynaptic marker), and neuroligin 1 and PSD95 (a postsynaptic marker) was performed by immunofluorescence staining. Images were merge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…To clarify potential mechanisms underlying GI dysfunction in neuroligin‐3 linked autism, we characterized expression of neuroligins and their binding partners, the neurexins, in the mouse GI tract. Neuroligins and neurexins are expressed in the rodent [Leembruggen et al, ; Wang et al, ] and human [Wang et al, ; Yang et al, ; Zhang et al, ] GI tract; however, little is known about the functional contribution of neuroligin‐3 expression in the GI tract. Nlgn1 , Nlgn2 , Nlgn3 , Nrxn1 , and Nrxn2 mRNAs are predominantly expressed in myenteric plexus‐enriched preparations of both duodenum and colon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify potential mechanisms underlying GI dysfunction in neuroligin‐3 linked autism, we characterized expression of neuroligins and their binding partners, the neurexins, in the mouse GI tract. Neuroligins and neurexins are expressed in the rodent [Leembruggen et al, ; Wang et al, ] and human [Wang et al, ; Yang et al, ; Zhang et al, ] GI tract; however, little is known about the functional contribution of neuroligin‐3 expression in the GI tract. Nlgn1 , Nlgn2 , Nlgn3 , Nrxn1 , and Nrxn2 mRNAs are predominantly expressed in myenteric plexus‐enriched preparations of both duodenum and colon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These mutations include genes encoding neuroligins, a group of four postsynaptic adhesion molecules (neuroligins‐1 to 4) and their extracellular and intracellular binding partners, neurexins and SHANK3 [Sudhof, ]. Expression of genes encoding several of these proteins is reported in the GI tract [Wang et al, , ; Yang et al, ; Zhang et al, ]; however a systematic analysis of expression in both the small and large intestine and, of particular interest, in neuronal enriched samples is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroligin proteins are present in enteric neurons [28][29][30] . As the enteric nervous system plays a major role in regulating gastrointestinal function, we postulated that the R451C mutation would affect motility.…”
Section: Representative Resultsmentioning
confidence: 99%
“…In the enteric nervous system (ENS) of rats, researchers found that NLGN1 was expressed and had a temporal correlation with the development of ENS, during which malformations might occur due to their disruptions [26]. Zhang et al found that the expression of NLGN1 decreased signi cantly in the intestinal stenosis in Hirschsprung Disease (HSCR) [27]. Decreased expression of NLGN1 may cause abnormal excitatory synaptic conduction, leading to continued contraction of diseased intestinal segments, and eventually the onset of HSCR.…”
Section: Discussionmentioning
confidence: 99%